School Associations and School Committees: Improving the Quality of Education at MTs Hidayatul Mubtadi'in South Lampung - Komalasari, Maya Ayu (Journal Corner of Education, Linguistics, and Literature, 2024)
In order for education goals to be achieved effectively, the community and stakeholders must be actively involved in education management. Parents of students, as an integral part of society and users of educational services, play an important role in improving the quality of education provided by schools. This collaboration fosters mutually beneficial relationships and is very important for improving educational standards in educational institutions. Therefore, the formation of a school committee must be a collaborative partner in implementing school programs. This research aims to explore the nature of the management partnership between MTs Hidayatul Mubtadi'in and its school committee. This research uses a qualitative descriptive methodology, utilizing data collection techniques such as interviews, observation and documentation. Research findings show that there is strong collaboration between schools and school committees in improving the quality of education, with ongoing coordination in planning academic and non-academic activities, as well as social and community initiatives. The committee acts as a school partner, providing guidance, support and supervision of school activities, while acting as a liaison between the school and parents. Through well-defined roles and a strong partnership with the MTs Hidayatul Mubtadi'in committee, various programs aimed at improving the quality of education can be implemented effectively, thereby realizing the school's vision and mission and ensuring the satisfaction of parents. However, this success really depends on the active role of both parties, especially in terms of communication, program planning and resource management. More synergistic efforts are needed between schools, school committees and the community in creating a better and more sustainable educational environment.